Analgesic and anti-inflammatory activities of leaf extract of Kydia calycina Roxb. - Baburao Bhukya, Rama Narsimha Reddy Anreddy, Carey M. William and Krishna Mohan Gottumukkala (Bangladesh Pharmacological Society, 2009)
The methanol extract of leaves of Kydia calycina Roxb. was screened for the analgesic (using hot plate test and acetic acid-induced writhing test in mice) and anti-inflammatory (using rat paw edema test) activity at the doses of 200 and 400 mg/kg body weight. A significant (p<0.0005) analgesic effect was observed with 200 mg/kg and 400 mg/kg in both tests. The maximum anti-inflammatory response was produced at 3 hour with extract doses of 200 and 400 mg/kg. These results suggest that the methanol extract of K. calycina has exhibited significant analgesic and anti-inflammatory effects, which were comparable with standard drugs.